2015
DOI: 10.3329/bjpt.v22i2.26074
|View full text |Cite
|
Sign up to set email alerts
|

Systematic implications of achene characteristics in genera <i>Centaurea</i> L., <i>Cyanus</i> Mill., <i>Psephellus</i> Cass. and <i>Rhaponticoides</i> Vaill. (Asteraceae)

Abstract: This study examines the exomorphic achene characteristics of 23 taxa belonging to Centaurea, Cyanus, Psephellus and Rhaponticoides in Asteraceae using light microscope and scanning electron microscope (SEM). The exomorphic characteristics studied are shape, size, colour and surface pattern of achene, and hair, length and colour of pappus. The results of the present investigation showed that achene size of the studied taxa is 3-7 × 1-4 mm. Pappus length is 1-14 mm, deciduous for three taxa and inner row is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Achene morphology is a diagnostic characteristic owing to the variation seen in specific and generic levels; therefore, achene morphology can make a distinction at the interspecific level (Szukala et al, 2019). Previous studies reported that achene micromorphology provides useful characteristics for the delimitation of different plant groups, and several achenes and pappus characteristics, achene shape, achene size, color, surface ornamentation, pappus color, length, and structure were suggested as useful in different taxonomic levels in the Asteraceae family (Bona, 2015; Candan et al, 2016; Özcan & Akıncı, 2019; Şirin et al, 2017). This study supports the utilization of achene micromorphology as a distinctive feature for the identification of species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Achene morphology is a diagnostic characteristic owing to the variation seen in specific and generic levels; therefore, achene morphology can make a distinction at the interspecific level (Szukala et al, 2019). Previous studies reported that achene micromorphology provides useful characteristics for the delimitation of different plant groups, and several achenes and pappus characteristics, achene shape, achene size, color, surface ornamentation, pappus color, length, and structure were suggested as useful in different taxonomic levels in the Asteraceae family (Bona, 2015; Candan et al, 2016; Özcan & Akıncı, 2019; Şirin et al, 2017). This study supports the utilization of achene micromorphology as a distinctive feature for the identification of species.…”
Section: Discussionmentioning
confidence: 99%
“…Microstructural characteristics are useful in particular for taxonomically complicated families (Bona, 2013; Karaismailoğlu, 2019; Özbek, Özbek, & Vural, 2018; Ullah et al, 2019). Analysis of micromorphological characteristics can help to acquire useful data for building an evolutionary approach among different taxonomic units (Bona, 2015; Luqman et al, 2019; Özüdoğru, Akaydın, Erik, & Mummenhoff, 2016; Rashid et al, 2018; Ullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological data from the pappus are taxonomically useful for assessing relationships among species and have helped to reveal evolutionary relationships among and within genera of Asteraceae (Mukherjee & Sarkar, 2001;Semple & Hood, 2003Semple, 2006;Abid & Zehra, 2007;Abid & Qaiser, 2007Mukherjee & Nordenstam, 2008;Bona, 2015;Şirin et al, 2017). It may also contribute to the wind-dispersal of the seeds (Azuma, 2006;Stille et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic usefulness of seed and fruit morphology is variable between plant groups; however, compared with many vegetative and floral structures, seed coat and fruit morphology show very low phenotypic plasticity and less affected by environmental conditions (Barthlott 1984;Zorić et al, 2010). Achenes of Asteraceae have a variety of shape, size, pappus, ribbing pattern and surface sculpturing, representing useful taxonomic tools for classification and delimitation of various taxa from species to tribal level (Zhu et al, 2006;Kreitschitz & Vallès, 2007;Mukherjee & Nordenstam, 2008;Savadkoohi et al, 2012;Roque & Funk, 2013;Zhang et al, 2013;Akcin & Akcin, 2014;Bona, 2015;Behjou et al, 2016;Ghimire et al, 2016;Karanovic et al, 2016;Şirin et al, 2017;Ozcan & Akinci, 2019).…”
Section: Introductionmentioning
confidence: 99%